The unique value of cardiovascular magnetic resonance in patients with suspected acute coronary syndrome and culprit-free coronary angiograms - Panovský, Roman; Borová, Júlia; Pleva, Martin; Feitová, Věra; Novotný, Petr; Kincl, Vladimír; Holeček, Tomáš; Meluzín, Jaroslav; Sochor, Ondřej; Štěpánová, Radka (BMC cardiovascular disorders, 2017)
BACKGROUND: Patients with chest pain, elevated troponin, and unobstructed coronary disease present a clinical dilemma. The purpose of this study was to investigate the incremental diagnostic value of cardiovascular magnetic resonance (CMR) in a cohort of patients with suspected acute coronary syndrome (ACS) and unobstructed coronary arteries. RESULTS: Data files of patients meeting the inclusion criteria in two cardiology centres were searched and analysed. The inclusion criteria included: 1) thoracic pain suspected with ACS; 2) a significant increase in the high-sensitive Troponin T value; 3) ECG changes; 4) coronary arteries without any significant stenosis; 5) a CMR examination included in the diagnostic process; 6) an uncertain diagnosis before the CMR exam; and 7) the absence of known CMR and contrast media contraindications. Special attention was paid to the benefits of CMR in determining the final diagnosis. In total, 136 patients who underwent coronary angiography for chest pain were analysed. The most frequent underlying causes were myocarditis (38%) and perimyocarditis (18%), followed by angiographically unrecognised acute myocardial infarction (18%) and Takotsubo cardiomyopathy (15%). The final diagnosis remained unclear in 6% of the patients. The contribution of CMR in determining the final diagnosis determination was crucial in 57% of the patients. In another 35% of the patients, CMR confirmed the suspicion and, only 8% of the CMR examinations did not help at all and had no influence on diagnosis or treatment. CONCLUSION: CMR provided a powerful incremental diagnostic value in the cohort of patients with suspected ACS and unobstructed coronary arteries. CMR is highly recommended to be incorporated as an inalienable part of the diagnostic algorithms in these patients.
Keywords: dospělí; Cardiac magnetic resonance; Magnetic Resonance Imaging; Acute Coronary Syndrome; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; Predictive Value of Tests; Reproducibility of Results; Normal coronary angiography; prediktivní hodnota testů; lidé; magnetická rezonanční tomografie; Critical Pathways; koronární angiografie; Algorithms; Electrocardiography; elektrokardiografie; prognóza; Troponin T; Humans; angina pectoris; reprodukovatelnost výsledků; nemoci koronárních tepen; Male; Acute coronary syndrome; Aged; Czech Republic; Angina Pectoris; kritické cesty; Coronary Artery Disease; algoritmy; Prognosis; Česká republika; lidé středního věku; senioři; akutní koronární syndrom; mužské pohlaví; Middle Aged; troponin T; Coronary Angiography